TRUST AND OPPORTUNISM IN A DYADIC PARTNERSHIP - Kokko, Lassi (My University, 2008)
This thesis studies trust and opportunism in a dyadic partnership. The objective is to explore trust and opportunism in a buyer-supplier partnership. In today's turbulent economy firms have to create genuine partnerships with each other to able to compete in today’s fast changing economy. Typical buyer-supplier relationships are not enough to be able to achieve all the possible benefits of cooperation. Opportunism is a behavioral assumption of transaction cost economics that can be described as the tendency to exploit partners in the zealous pursuit of self-interest with guile. In this study trust is defined as a phenomenon that will reduce transaction costs as higher level of trust is attained. The theoretical framework of this study is formed according to theories of partnership, opportunism and trust. The framework suggest that trust develops in a dyadic partnership as time passes and when partners overcome mutual struggles in the partnership. The empirical research was conducted by a descriptive-explanatory case study, where a single buyer-supplier partnership was chosen to be researched. Interviews were conducted in both companies. The object was to let respondents talk freely and open semi-structured interview were seen as the best option for this purpose. Other valuable qualitative data was gathered from meeting memos and seminar lectures. The collected data was carefully analyzed. The findings prove that lack of trust can easily lead to opportunistic behavior. The findings also prove that when partners openly discuss and solve these problems the trust is gained. Having mutual struggles and ability to overcome these together will have an enormous boost to trust in a dyadic partnership. Practical contributions suggest that partners should implement a feedback system that hastens the feedback process. Partners should also increase open communication in all organization levels. Finally, partners in buyer-supplier relationships should regularly discuss about capacity, volumes and future plans of cooperation.
Keywords: Opportunism; Trust; Partnership; Transaction Cost Economics.; fi=Johtaminen ja organisaatiot|en=Management and Organization|